If you make it wrong, fix it: an experimental study on health news in G1 and WhatsApp - Gramacho, Wladimir; Garcia, Rebeca; Behnke, Emilly; Gomes, Victor (Brazilian journalism research, 2022)
ABSTRACT - This article analyzes the effect of news reports containing grammatical errors that have been corrected or updated, how readers perceive the credibility of this information, and their behavioral intention with the content in the news reports. We investigated these effects in a report on yellow fever vaccination with a sample of 1.648 individuals. Based on an experimental research design, we measured the effects of the vehicle (G1 or WhatsApp) and five versions of a text. The findings show that the same text assigned to G1 or a WhatsApp message was perceived as more credible in the first case. Grammatical errors, updates, and corrections, in general, did not affect the credibility of the news or the intention to be vaccinated. When the news is attributed to the G1, however, the credibility of the “corrected” message is significantly higher than the credibility of the message with serious grammar errors. RESUMO – Este artigo analisa o efeito de notícias com erros gramaticais, corrigidas ou atualizadas sobre a percepção de leitoras e leitores em relação à credibilidade da informação e sobre sua intenção de comportamento associada ao conteúdo dessa notícia. Investigamos esses efeitos em uma notícia sobre a vacinação contra a febre amarela junto a uma amostra de 1.648 indivíduos. Com base num desenho experimental, mensuramos os efeitos do veículo (G1 ou WhatsApp) e de cinco versões de um texto. Os achados mostram que o mesmo texto atribuído ao G1 ou a uma mensagem de WhatsApp foi percebido como mais credível no primeiro caso. Erros gramaticais, atualizações e correções em geral não afetaram a credibilidade da notícia nem a intenção de vacinação das participantes. Quando a notícia é atribuída ao G1, porém, a credibilidade da mensagem “corrigida” é significativamente maior que a credibilidade da mensagem com erros graves de gramática. RESUMEN – Este artículo analiza el efecto de noticias con errores gramaticales, corregidas o actualizadas sobre la percepción de las lectoras y de los lectores con relación con la credibilidad de la información y sobre su intención de comportamiento asociada al contenido de esa noticia. Investigamos esos efectos en una nota sobre la vacunación contra la fiebre amarilla con una muestra de 1.648 individuos. A partir de un diseño experimental, medimos los efectos del medio (G1 o WhatsApp) y de cinco versiones de un texto. Los hallazgos muestran que el mismo texto asociado a G1 o a un mensaje de WhatsApp se percibió como más creíble en el primer caso. Los errores gramaticales, actualizaciones y correcciones generalmente no afectaron la credibilidad de la noticia ni la intención de vacunación. Cuando la noticia se atribuye al G1, todavía, la credibilidad del mensaje “corregido” es significativamente mayor que la credibilidad del mensaje con graves errores gramaticales.